Emergency residents' self-perceived readiness for practice: the association of milestones, entrustable professional activities, and professional identities—a multi-institutional survey - Chang, Yu-Che; Khwepeya, Madalitso; Nkambule, Nothando S.; Chuang, Renee S.; Chaou, Chung-Hsien (Frontiers in Medicine, 2023)
Background As a successful innovation, competency-based medical education and its assessment tools continue to be a key strategy in training future doctors and tracking their performance trajectories. Linked to professional identity, evidence suggests that clinical competence is related to thinking, acting and feeling like a physician. Thus, incorporating the values and attitudes of healthcare professions as part of their professional identity in the clinical workplace improves professional performance. Methods Through a cross-sectional study, we examined the association of milestone, entrustable professional activities (EPA) and professional identity using self-reported tools among emergency medicine residents from 12 teaching hospitals across Taiwan. Milestone, EPA and professional identity were assessed using the Emergency Medicine Milestone Scale, Entrustable Professional Activity Scale and Emergency Physician Professional Identity and Value Scale, respectively. Results The results of a Pearson correlation indicated a significant positive correlation between milestone-based core competencies and EPAs (r = 0.40 0.74, p < 0.01). The professional identity domain of skills acquisition, capabilities and practical wisdom was positively correlated with milestone-based core competencies of patient care, medical knowledge, practice-based learning and improvement, and system-based practice (r = 0.18 0.21, p ≤ 0.05), and six items of EPA (r = 0.16 0.22, p < 0.05). Additionally, the professional identity domain of professional recognition and self-esteem was positively correlated with practice-based learning and improvement, and system-based practice milestone competencies (r = 0.16 0.19, p < 0.05). Conclusion This study demonstrates milestone and EPA assessment tools are highly linked and therefore, can be synergistically used by supervisors and clinical educators to evaluate clinical performance during residency training. Emergency physicians’ professional identity is partly influenced by the advancement of skills and a resident’s ability to learn, effectively perform tasks and make appropriate medical decisions at the system level in their clinical practice. Further research is warranted to understand the importance of residents’ competency in relation to their professional identity development trajectory during clinical training.